Physico-mechanical performance and durability of artificial lightweight aggregates synthesized by cementing and geopolymerization. (30th January 2020) - Ul Rehman, Munib; Rashid, Khuram; Ul Haq, Ehsan; Hussain, Murid; Shehzad, Nasir
Highlights: Lightweight aggregates (LWAs) were synthesized by cementing and geopolymerization. Physical-mechanical properties and durability of LWAs were investigated. Both types of LWAs were light in weight and good in strength. Both types of LWAs showed resistance against ASR expansion. The discussion on ASR was strengthened by XRD and FTIR analysis. Abstract: This study encompasses production of lightweight aggregates (LWAs) through cold bonded pelletization using two different industrial by-products; coal fly ash (FA) and ground granulated blast furnace slag (GBFS). Two distinct types of LWAs were produced by two different binders; one by using cement (cement based (CB) aggregates) and the other by using geopolymerization method (geopolymer (GP) aggregates). Different curing conditions were adopted in this experimental work, their influence on physical and mechanical properties were investigated through density, water absorption, aggregate impact value and ten percent fines value tests. Durability of LWAs was assessed by conducting alkali silica reaction (ASR) test on cement mortar and geopolymer mortar by incorporating both types of LWAs. The crystalline natures and the types of bonding were assessed by using petrographic analysis, x-ray diffraction (XRD) and Fourier-transform infrared spectroscopy (FTIR). Results demonstrated that artificially produced LWAs were lighter than many previously manufactured cold bonded and sintered LWAs, and consequently experienced slightly higher water absorption. However, water absorption values for both types, were within the acceptable limits (less than25%) as recommended by ACI. Aggregate impact value and ten percent fines value test results indicated that CB aggregates were stronger than GP aggregates. ASR test results along with petrographic thin sections study, XRD and FTIR analysis results revealed that LWAs were not reactive and can be safely used in both types of concrete, conventional and geopolymeric. The study concludes, produced LWAs can be effectively used as a replacement of natural coarse aggregate in formulation of structural lightweight concrete with many technical, economic and environmental benefits.